Occurrence of Anaemia in the First Year of Inflammatory Bowel Disease in a European Population-based Inception Cohort-An ECCO-EpiCom Study - Burisch, Johan; Vegh, Zsuzsanna; Katsanos, Konstantinnos H; Christodoulou, Dimitrios K; Lazar, Daniela; Goldis, Adrian; O'Morain, Colm; Fernandez, Alberto; Pereira, Santos; Myers, Sally; Sebastian, Shaji; Pedersen, Natalia; et al. (Journal of Crohn's and colitis, 2017)
Background and aims: Anaemia is an important complication of inflammatory bowel disease [IBD]. The aim of this study was to determine the prevalence of anaemia and the practice of anaemia screening during the first year following diagnosis, in a European prospective population-based inception cohort. Methods: Newly diagnosed IBD patients were included and followed prospectively for 1 year in 29 European and one Australian centre. Clinical data including demographics, medical therapy, surgery and blood samples were collected. Anaemia was defined according to the World Health Organization criteria. Results: A total of 1871 patients (Crohn's disease [CD]: 686, 88%; ulcerative colitis [UC]: 1,021, 87%; IBD unclassified [IBDU] 164. 81%) were included in the study. The prevalence of anaemia was higher in CD than in UC patients and, overall, 49% of CD and 39% of UC patients experienced at least one instance of anaemia during the first 12 months after diagnosis. UC patients with more extensive disease and those from Eastern European countries, and CD patients with penetrating disease or colonic disease location, had higher risks of anaemia. CD and UC patients in need of none or only mild anti-inflammatory treatment had a lower risk of anaemia. In a significant proportion of patients, anaemia was not assessed until several months after diagnosis, and in almost half of all cases of anaemia a thorough work-up was not performed. Conclusions: Overall, 42% of patients had at least one instance of anaemia during the first year following diagnosis. Most patients were assessed for anaemia regularly; however, a full anaemia work-up was frequently neglected in this community setting.
Keywords: dospělí; Female; Anemia; Adult; mladý dospělý; ženské pohlaví; Adolescent; Inflammatory Bowel Diseases; lidé; Aged, 80 and over; Colitis, Ulcerative; Crohn Disease; prospektivní studie; Male; Aged; Prospective Studies; Young Adult; ulcerózní kolitida; idiopatické střevní záněty; lidé středního věku; Crohnova nemoc; senioři nad 80 let; senioři; anemie; mužské pohlaví; Middle Aged; mladiství; Humans